2012
DOI: 10.1002/gcc.22032
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free microRNAs as diagnostic, prognostic, and predictive biomarkers for lung cancer

Abstract: Lung cancer is the most common cancer worldwide, accounting for over 1.37 million deaths annually. The clinical outcome and management of lung cancer patients could be substantially improved by the implementation of non-invasive biomarker assays for the early detection, prognosis as well as prediction and monitoring of treatment response. MicroRNAs (miRNAs) have been implicated in the regulation of virtually all signaling circuits within a cell and their dysregulation has been shown to play an essential role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 79 publications
0
50
0
Order By: Relevance
“…A single tumour tissue sample obtained by biopsy is not fully representative of the molecular changes occurring in developing lung cancers, nor does it reflect the diversity of tumour clones found in distant metastases. In this case, analysis of extracellular miRNAs should not only enable disease monitoring but also allow for effective treatment monitoring, which seems to be a key factor in improving prognosis [72]. Extracellular miRNA sequences might also be an early marker of recurrence after radical treatment.…”
Section: Extracellular Mirnamentioning
confidence: 99%
“…A single tumour tissue sample obtained by biopsy is not fully representative of the molecular changes occurring in developing lung cancers, nor does it reflect the diversity of tumour clones found in distant metastases. In this case, analysis of extracellular miRNAs should not only enable disease monitoring but also allow for effective treatment monitoring, which seems to be a key factor in improving prognosis [72]. Extracellular miRNA sequences might also be an early marker of recurrence after radical treatment.…”
Section: Extracellular Mirnamentioning
confidence: 99%
“…Despite intensive researches and resources being dedicated to elucidate the molecular mechanisms of NSCLC, the precise processes of initiation and progression remain largely unclear. Recently, accumulating evidence has shown that non-coding small RNAs may be involved in NSCLC pathogenesis, providing new insights into lung tumor biology [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can regulate cancer cell differentiation, proliferation, survival, and metastasis, acting as oncogenes or tumor suppressors by regulating the expression of downstream genes through different cancer development and progression pathways (Chen, 2005;Garzon et al, 2009;Kwak et al, 2010;Zandberga et al, 2013). Accordingly, these molecules could constitute a powerful therapeutic strategy for interfering with cancer initiation and progression (Garofalo and Croce, 2011).…”
Section: Monitoring Micrornas Using a Molecularmentioning
confidence: 99%